Pengaruh Motivasi Kerja dan Kompetensi Kerja terhadap Prestasi Salesman : Studi pada Salesman Kota Pontianak - Annas Rahmat Ramadhani; Ryovaldo Evan Angello (AKUNTANSI 45, 2025)
The implementation of this research has the purpose of understanding the influence of work motivation and work competence on the performance and achievements of salesmen in Pontianak City who sell products in traditional markets, retail and wholesale stores. This study is aimed at seeing the influence that occurs between one variable and a number of other variables that are being studied. The sampling method used is random sampling to provide an equal opportunity for all population members to be selected as samples. The salesmen surveyed distributed snacks, beverages, and essential goods, with a total of 31 participants. Multiple linear regression is applied to this study as an analysis method. After the data analysis was carried out, it was found that it work motivation did not affect salesman performance, while work competence had a positive effect on salesman performance. In addition, simultaneously, work motivation and competence had a positive effect on the performance of salesmen of snacks, beverages and basic necessities in the Pontianak area who sold in traditional markets, retail stores and wholesalers.